Revision of the British record of Tropidemys (Testudines,Plesiochelyidae) and recognition of its presence in the Late Jurassic of Portugal - Pérez-García, A. (Journal of Iberian Geology, 2015)
The record of coastal marine turtles belonging to Plesiochelyidae is abundant in the Late Jurassic of Portugal. The material analyzed thus far has been attributed to two taxa: Plesiochelys and Craspedochelys. A specimen is presented here that allows extending the known diversity of Portuguese Jurassic turtles. It is attributed to Tropidemys. Although this taxon is relatively well known in the Kimmeridgian record of Switzerland and Germany, no specific allocation performed outside these countries can be, so far, confirmed. The detailed study of the poorly known British taxon “Pelobatochelys” blakii allows its specific validity to be confirmed here, being recognized as a member of Tropidemys. The revision of this species and the analysis of the new Portuguese specimen allow extending the knowledge regarding the genus Tropidemys.